The effect of moderate period exercises using multiple punching device according to physiological variables to qualify people with insulin-dependent diabetes - Haidar, Alaa Khalaf; Mahmoud, Ahmed Shaker; Abdulla, Ali Talal; Ahmed, Omar Saad (International Journal of Psychosocial Rehabilitation, 2020)
The effect of moderate periodical exercises using the multiple punching system according to physiological variables to qualify people with insulin-dependent diabetes. The research procedures were carried out using the experimental method on a sample of (9) diabetics aged (35-45 years) from the city of Baghdad. The researchers used moderate periodical exercises using the multi-punching device according to physiological variables, and the pre and post tests were done using both the ONE TOUCH PROFILE device.The researchers reached several conclusions, the most important of which were :Moderate period exercises using the multiple punching device according to physiological variables with a positive effect in the rehabilitation of people with diabetes (type II) that are not dependent on insulin in terms of health.The moderate period exercises using the multiple punching device according to physiological variables contributed to increasing the sensitivity of the cells of the patients ’bodies within the research sample to the hormone insulin by reducing the peripheral resistance of the cells to the effect of the hormone insulin, as well as increasing the functional ability and improving the biological effect of the hormone insulin in the percentage of glucose in the blood.